Increased PD-1 Expression on Circulating T Cells Correlates with Inferior Outcome after Autologous Stem Cell Transplantation - Richter, Silja; Böttcher, Martin; Stoll, Andrej; Zeremski, Vanja; Völkl, Simon; Mackensen, Andreas; Ekici, Arif Bülent; Jacobs, Benedikt; Mougiakakos, Dimitrios (Transplantation and Cellular Therapy, 2024)
High-dose chemotherapy followed by autologous stem cell transplantation (auto-SCT) is a well-established treatment option for multiple myeloma and malignant lymphoma patients. It is able to induce long-term progression-free survival (PFS) in both patient groups and even provide a cure in patients with aggressive lymphoma. However, relapse is common and has been associated with the pace and quality of immunologic reconstitution after transplantation, as well as with immune cell exhaustion and immunometabolic defects. We aimed to analyze the dynamics of the prototypical exhaustion marker PD-1 on immune cells during reconstitution on high-dose chemotherapy followed by auto-SCT and its impact on PFS. We performed a comprehensive analysis of exhaustion and metabolic markers on immune cells from myeloma and lymphoma patients undergoing auto-SCT using flow cytometry and NanoString technologies. The expression levels of PD-1 were increased during early reconstitution after transplantation on T cells and natural killer (NK) cells, as well as on monocytes. However, while PD-1 expression in NK cells and monocytes normalized over time, PD-1 expression on T cells demonstrated a variable course. Of note, lymphoma patients with continuously increasing PD-1 expression on T cells after auto-SCT had an inferior median PFS of only 146 days, whereas the median PFS was not reached in the lymphoma patients without such a PD-1 expression pattern. T cells from patients with increased PD-1 expression after auto-SCT exhibited an immunometabolic (over)activation and exhausted phenotype compared to T cells from patients with a low PD-1 expression after transplantation, including higher levels of the glycolytic pacemaker enzyme hexokinase 2 and the inhibitory receptor CTLA-4. In addition, proliferating Ki-67+ T cells were more abundant in patients with high PD-1 expression on T cells compared to those with low expression after auto-SCT (11.9% versus 4.2%). PD-1 expression on T cells might serve as an adverse biomarker for lymphoma patients undergoing auto-SCT; however, further validation by larger prospective studies is required.
CRIS-Team Scopus Importer:2024-04-12
Keywords: auto-SCT; exhaustion; PD-1; T cells

Oxidative DNA damage in reconstituting T cells is associated with relapse and inferior survival after allo-SCT - Karl, Franziska; Liang, C.; Böttcher-Loschinski, R.; Stoll, Andrej; Flamann, Cindy; Richter, Silja; Lischer, Christopher; Völkl, Simon; Jacobs, Benedikt; Böttcher, M.; Jitschin, R.; Bruns, Heiko; et al. (Blood, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-SCT) is the only curative treatment option for a number of hematologic malignancies. Its therapeutic potential relies on the potency of donor T cells to eliminate residual malignant cells, the so-called graft-versus-leukemia (GVL) effect. Disease relapse remains the most frequent treatment failure and is associated with poor outcome. Therefore, it is inevitable to decipher mechanisms that weaken GVL. In recent years, studies of tumor biology have revealed that metabolic remodeling of the micromilieu can critically regulate immune responses. Accumulation of reactive oxygen species leads to a metabolic condition known as oxidative stress, which can severely hamper T cells. Currently, only a few studies, mainly using preclinical models, have demonstrated the occurrence of oxidative stress after allo-SCTs. Therefore, we sought to investigate oxidative stress in a well-characterized group of patients who underwent allo-SCT and its impact on reconstituting T cells. We identified high concentrations of serum 8-hydroxydeoxyguanosine (8-OHdG) as an established biomarker for oxidative stress. 8-OHdG is one of the major products of DNA oxidation, which is normally rapidly removed. After allo-SCT, T cells accumulated oxidative DNA damage. High cellular 8-OHdG content (8-OHdGhi) was associated not only with signs of enhanced T-cell activation but also premature exhaustion. The inability of 8-OHdGhi T cells to efficiently target malignant cells or produce cytotoxic granzyme B and interferon gamma was associated with a significantly increased relapse risk and a shorter overall survival. Taken together, our novel findings could give reason to focus on bolstering DNA repair in reconstituting T cells as a means to improve GVL efficacy.
CRIS-Team Scopus Importer:2023-03-31

The metabolic profile of reconstituting T-cells, NK-cells, and monocytes following autologous stem cell transplantation and its impact on outcome - Richter, Silja; Böttcher, Martin; Mackensen, Andreas; Ullrich, Evelyn; Jacobs, Benedikt; Mougiakakos, Dimitrios; Völkl, Simon (Scientific Reports, 2022)
Previous studies indicated a role of the reconstituting immune system for disease outcome upon high-dose chemotherapy (HDCT) and autologous stem cell transplantation (auto-SCT) in multiple myeloma (MM) and lymphoma patients. Since immune cell metabolism and function are closely interconnected, we used flow-cytometry techniques to analyze key components and functions of the metabolic machinery in reconstituting immune cells upon HDCT/auto-SCT. We observed increased proliferative activity and an upregulation of the glycolytic and fatty acid oxidation (FAO) machinery in immune cells during engraftment. Metabolic activation was more pronounced in T-cells of advanced differentiation stages, in CD56bright NK-cells, and CD14++CD16+ intermediate monocytes. Next, we investigated a potential correlation between the immune cells’ metabolic profile and early progression or relapse in lymphoma patients within the first twelve months following auto-SCT. Here, persistently increased metabolic parameters correlated with a rather poor disease course. Taken together, reconstituting immune cells display an upregulated bioenergetic machinery following auto-SCT. Interestingly, a persistently enhanced metabolic immune cell phenotype correlated with reduced PFS. However, it remains to be elucidated, if the clinical data can be confirmed within a larger set of patients and if residual malignant cells not detected by conventional means possibly caused the metabolic activation.
CRIS-Team Scopus Importer:2022-07-15